Kontribusi Tinggi Badan, Rentang Lengan, Kekuatan Otot Lengan dan Otot Tungkai, Serta VO2Max Terhadap Prestasi Mendayung Mesin Rowing Jarak 2000 Meter Pada Atlet Dayung Nasional (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The problem in this research were 1) Is there a height contributes to achievement of rowing machine rowing 2000 meters distance. 2) Is there a arms lenght contribution to the achievement of a rowing machine rowing 3) Is there an arm muscle strength contributes to the achievement of rowing 4) Is there a leg muscle strength contributes to the achievement of a rowing machine rowing 5) are there any VO2max contribution to the achievement Max rowing machine rowing 6) which one has contribution greater than height, arm length, arm muscle strength and leg muscles, as well as VO2 Max to achievement rowing machine rowing The results of data analysis showed that height contributes to achievement of rowing machine rowing 38.1%. Contribution to the achievement of the arm lenght rowing to machine rowing 35.9%. Contribution to the achievement of the strength of the arm muscles rowing machine rowing 40.4%. Leg muscle strength contributes to the achievement of a rowing machine rowing 45.3%. Contributions VO2Max the achievement of rowing machine rowing 51.5%. contribution of height, arm length, arm muscle strength and leg muscles as well VO2Max the distance rowing machine rowing achievements in 2000 by 66.6%